PDTM-29. CSF H3F3A K27M CIRCULATING TUMOR DNA COPY NUMBER QUANTIFIES TUMOR GROWTH AND TREATMENT RESPONSE. (5th November 2018) - Stallard, Stefanie; G. Savelieff, Masha; Mullan, Brendan; Miklja, Zachary; Bruzek, Amy; Garcia, Taylor; Wierzbicki, Kyle; Singer, Benjamin; Hashizume, Rintaro; Montero Carcaboso, Angel; Q. McMurray, Kaitlin; Heth, Jason; et al.
Abstract: Primary brain tumors and CNS metastases shed circulating tumor DNA (ctDNA) into the CSF, which can be assessed for tumor-associated mutations. Thus far, there have been no extensive studies using droplet digital PCR (ddPCR) to detect and quantify ctDNA in the CSF of pediatric high-grade brain tumor patients. There are also gaps in our knowledge, including the potential dependence of ctDNA amount on location of sample collection and whether ctDNA can be used to quantify tumor growth and treatment response. To address these questions, we developed a novel H3F3A K27M ddPCR assay and applied it to four pediatric patients with H3F3A K27M-mutant DIPG and GBM. We found that ddPCR was able to detect the K27M mutation in patient CSF and that the closest relation emerged between mutant K27M copies per ng of total DNA (henceforth K27M copies) and contrast-enhancing tumor area on MRI. Multi-focal CSF sampling at autopsy of a DIPG patient exhibited differences in K27M copies by proximity to the tumor. To better understand changes in K27M copies in response to both growth and treatment of DIPG, we developed an in vitro system comprised of astrocytes (NHAs) co-cultured with luciferase-expressing human DIPG cell line DIPG007 as a means to simulate ctDNA release into the CSF. We found that DIPG007 cells released ctDNA into culture media in proportion to their proliferation, even when the media was changed frequently to approximate the constant production and resorption of CSF. Irradiation with 8 Gy resulted in a spike in mutant ctDNA 72–120 hours post-radiotherapy before decreasing. In summary, our study suggests that H3F3A K27M copies in the CSF of children with high-grade brain tumors have a linear relation with contrast-enhancing tumor area and that ddPCR can be used to follow treatment response including ctDNA release shortly after effective therapies.